Inclusive and Personalization: Reinterpreting Christian Education Learning Planning Based on the Merdeka Curriculum - Panggabean, Justice Zeni Zari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study investigates the implementation of an inclusive and personalized curriculum in Christian Religious Education at SD Negeri 178492 Pagar Batu Village, North Tapanuli. This study employed a qualitative approach with 23 participants, comprising teachers and students. The findings reveal that the curriculum effectively promoted inclusivity by addressing students' diverse learning needs, backgrounds, and spiritual development. Teachers employed various instructional strategies, such as differentiated tasks and flexible group discussions, while adapting lesson plans to individual interests and abilities. Students appreciated the opportunities to personalize their learning experiences and connect them with religious teachings. However, the study also identified challenges, including limited resources, insufficient training in inclusive education strategies, and inconsistent personalized instruction across different classes. Overall, the research highlights that while the curriculum’s inclusive and personalized approach was largely successful, there remains a need for strengthened professional development and resource support to enhance its consistent and effective application.